2002
DOI: 10.1046/j.1365-2664.2002.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil seed banks and the effects of meadow management on vegetation change in a 10‐year meadow field trial

Abstract: Summary1. Enhancement of plant species diversity is often an objective in grassland management for wildlife conservation. Such management regimes may also change the species composition of soil seed banks, which may themselves affect future vegetation change. We compared soil seed banks and vegetation from a long-term meadow management trial and from a series of traditionally managed species-rich meadows in northern England, UK. 2. The management trial used three hay-cut date treatments (14 June, 21 July and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 35 publications
6
69
3
Order By: Relevance
“…Usually, seed densities in the upper soil layer are higher than in the lower layer (Thompson et al 1997;Smith et al 2002). We observed the opposite tendency in fens and degraded meadows.…”
Section: Changes In Spectra Of Regeneration-related Traitscontrasting
confidence: 44%
“…Usually, seed densities in the upper soil layer are higher than in the lower layer (Thompson et al 1997;Smith et al 2002). We observed the opposite tendency in fens and degraded meadows.…”
Section: Changes In Spectra Of Regeneration-related Traitscontrasting
confidence: 44%
“…Consequently, these data points could only be included in the MA assessing response ratio. Two suitable studies on seed shed and seed bank were also found, but not included because their very specific focus was too marginal with respect to our main research question [20,57]. There was no single study on birds that complied with our selection criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Mowing vegetation at least once a year has a positive effect on vascular plant species richness, especially when cuttings are removed [17,18]. However, since it has been demonstrated that early-summer mowing often has a detrimental effect on species richness of flowering plants, as it hampers completion of the reproductive cycle [17], later mowing is generally found to be more favourable for vascular plant biodiversity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…While official estimates suggest that as many as 97% (NCC, 1984) The relevance of these locally-embedded understandings is highlighted when 'lost' hay meadows are considered. Pinpointing the previous location of hay meadows is crucial for the practice of reinstating hay meadows from former seed banks (see Smith et al 2002).…”
Section: Records From the Groundmentioning
confidence: 99%